The Role Of Leadership Skills For Managers' Pan Of Education Educational Governorates In The Sultanate Of Oman In Raising The Efficiency Of Managers And Job Satisfaction - Mahmoud Mohammed Ali; Rashid Abdalhamaid Kirembwe; Hamid Salim Said Al Noumani (International Journal of Scientific and Technology Research, 2024)
Non-Indexed Publication